Perlindungan Hukum Bagi Konsumen atas Penjualan Produk Obrak Online - Dewa Gede Widya Swastika; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Indonesia is a developing country which one of the aspects that greatly influence its development is in the field of economy, in this case covering the field of trade. The existence of free trade is not little among businesses conducting unhealthy competition, especially for traded products. This research discusses two problem namely first, how the legal protection for consumers against the sale of online sale products without clear information and secondly, how are business actors responsible for consumers who experience losses due to online sale product purchases. Normative research is a type of research used in this study using a statutory approach. With this phenomenon it is impossible for people to be separated from the influence of business and as a consequence, society is the consumer who is the target of the producers. the lack of knowledge of the consumer community regarding their rights and obligations, it is necessary to further socialize the various provisions in Law Number 8 of 1999 concerning Consumer Protection. So that it is hoped that it can increase awareness, knowledge and independence of consumers to protect their interests, which in turn can foster an honest and responsible attitude of business actors, especially in terms of selling products through social media or online.